The “Chopsticks” Method: A Technique for Capsular Retraction During Hip Arthroscopy Utilizing Switching Sticks - Alec E. Winzenried MD; Kyle R. Wagner MD; Lucas McLean MD; Andrea M. Spiker MD (Video Journal of Sports Medicine)
Background: Hip arthroscopy has become an effective method for treating several symptomatic disorders of the hip, which includes femoroacetabular impingement (FAI). Capsulotomy is often necessary for visualization of hip pathology; however, this presents multiple challenges in both capsular management intraoperatively and final capsule closure. Current techniques include use of capsular suspension sutures to provide adequate views of the central and peripheral compartments. We present an atraumatic technique that may be used in conjunction with suspension sutures to decrease the need for excessive capsular debridement, additional personnel, and risk of injury for adequate visualization. Indications: Indications for using the “chopsticks” method for capsular retraction include patients with FAI who require osteochondroplasty or debridement of pathology within the peripheral compartment during hip arthroscopy. Technique Description: The patient is positioned supine with post-free traction applied. An anterolateral portal is established, followed by a modified mid-anterior portal under direct visualization. An interportal cut is performed for better visualization and access. A diagnostic arthroscopy of the central compartment is performed, and pathology is addressed as needed, including labral repair, subspine decompression or pincer resection, and chondroplasty. Traction is subsequently released, and if needed for visualization, a T-capsulotomy is performed to separate the medial and lateral limbs of the iliofemoral ligament with the knee and hip under slight flexion. Two switching sticks are inserted in the anterolateral portal. With the camera in the modified mid-anterior portal, 1 switching stick is placed intracapsular laterally (between the femoral neck and capsule) while the other is placed intracapsular medially (between the femoral neck and capsule) to retract the capsule and allow for osteochondroplasty. Complete capsular closure is performed following adequate cam decompression and removal of debris. Results: Careful retraction of the capsule intraoperatively decreases the need for excessive capsular debridement and retains adequate tissue for repair of the capsule at the end of the procedure. Numerous cadaveric and clinical studies have shown the importance of capsular closure in optimizing post-operative outcomes and, similarly, the importance of decreasing iatrogenic injury to the capsule intraoperatively. This also decreases the need of additional personnel in the operating room as capsular suspension sutures can require an assistant to hold traction to improve visualization or, in other cases, an assitant must flex/extend/internally and externally rotate the leg in order to achieve adequate visualization of the femoral head-neck junction. Discussion: The “chopsticks” method of capsular retraction presents a technically straightforward, economic approach to capsular retraction and allows for better visualization of cam deformities for resection. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.